Development of solid phase extraction with carbon nanoonion-polyaniline composite sorbent followed by microextraction method for the extraction of pesticides residues before gas chromatography - Zahra Shokouhmandi; Ardeshir Shokrollahi (Materials Research Express, 2022)
Organophosphate and triazole compounds are among the pesticides and fungicides that are classified as highly toxic materials because of their chronic and dangerous effects at low and moderate oral doses. Therefore, the measurement and extraction of small amounts of these compounds are of great importance for human and environmental health. In the present study, solid-phase extraction (SPE) was performed with carbon nano onion (CNO)-polyaniline (PANI) nanocomposite sorbent for the extraction of residual organic pesticides before gas chromatography (GC), so CNO was synthesized and covered with a layer of PANI for this purpose. The synthesized sorbent was analyzed and studied using different characterization methods. The prepared sorbent was used to extract pesticides from an aqueous medium. Then, for further preconcentration, the eluent of the SPE column was followed by a dispersive liquid-liquid microextraction (DLLME) method that had acceptable repeatability to the point that a wide linear range in 0.1–1000 μ g l ^−1 (R ^2  > 0.99) was obtained for most analytes. Finally, pesticides determination in rainwater, apple juice, and cherry juice samples was conducted by the developed method.